Learning Curve in Robotic Primary Ventral Hernia Repair Using Intraperitoneal Onlay Mesh: A Cumulative Sum Analysis. Issue 3 (June 2021) - Kudsi, Omar Y.; Gokcal, Fahri; Bou-Ayash, Naseem; Crawford, Allison S.; Chung, Sebastian K.; Chang, Karen; Litwin, Demetrius
Abstract : Background: Cumulative sum (CUSUM) learning curves (LCs) are useful to analyze individual performance and to evaluate the acquisition of new skills and the evolution of those skills as experience is accumulated. The purpose of this study is to present a CUSUM LC based on the operative times of robotic intraperitoneal onlay mesh (rIPOM) ventral hernia repair (VHR) and identify differences observed throughout its phases. Materials and Methods: Patients who underwent rIPOM repair for elective, midline, and primary hernias were included. All procedures were performed exclusively by one surgeon within a 5-year period. CUSUM and risk-adjusted CUSUM were used to visualize the LC of rIPOM-VHR, based on operative times and complications. Once groups were obtained, univariate comparisons were performed. Results: Of the 90 rIPOM repairs, 25, 40, and 25 patients were allocated using a CUSUM analysis to the early, middle, and late phases, respectively. In terms of skin-to-skin times, the middle phase has a mean duration of 23 minutes shorter than the early phase ( P <0.001), and the late phase has a mean duration 34 minutes shorter than the early phase ( P <0.001). A steep decrease in off-console time was observed, with a 10-minute difference from early to middle phases. A consistent and gradual decrease in operative times was observed after completion of 36 cases, and a risk-adjusted CUSUM revealed improving outcomes after 55 cases. Conclusions: This study demonstrates and elucidates interval improvement in operative efficiency in rIPOM-VHR. Consistently decreasing operative times and simultaneous accumulated complication rates were observed after the completion of 55 cases.